2015
DOI: 10.1159/000430279
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Trypsin Inhibitor Attenuates Acute Lung Injury by Improving Endothelial Progenitor Cells Functions

Abstract: Background: Urinary Trypsin Inhibitor (UTI) is involved in various aspects of tissue repair, regeneration and development. However, the potential role of UTI in protection against acute lung injury (ALI) remains largely unknown. In the present study, we demonstrated that UTI treatment could ameliorate ALI induced by oleic acid (OA) treatment in rabbit model. Methods: Intravenous application of UTI (10000 U/kg/d) significantly improved the pathologies associated with OA-induced ALI. The lungs were stained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…ALI is characterized by hypoxemia, rupture of alveolar capillary membranes, and pulmonary edema. Acute respiratory distress syndrome is a severe form of ALI, leading to a mortality rate of up to 40% . It has been shown that overexpression of CXCR4 in neutrophils can cause stem cell death .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALI is characterized by hypoxemia, rupture of alveolar capillary membranes, and pulmonary edema. Acute respiratory distress syndrome is a severe form of ALI, leading to a mortality rate of up to 40% . It has been shown that overexpression of CXCR4 in neutrophils can cause stem cell death .…”
Section: Discussionmentioning
confidence: 99%
“…Acute lung injury (ALI) is a fatal syndrome which may cause acute hypoxemic respiratory failure characterized by diffuse alveolar damage, increased permeability of alveolar capillaries, edema, pulmonary inflammation, and alveolar epithelial cell (AEC) apoptosis . Studies have shown that apoptosis of type II AECs may cause damage to epithelial barriers, which further leads to ALI . Lipopolysaccharide (LPS), a component of the cell wall of Gram‐negative bacteria, is closely related to AEC apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reviewed the protective reagents and methods for EPCs including tripterine, urinary trypsin inhibitor, microRNA-130a, interruption of CD40 pathway, and GM-CSF [68][69][70][71]. As a cholesterol-lowering medicine originally, probucol significantly inhibits the initiation and development of atherosclerosis via multiple mechanisms including suppressing ROS formation [72][73][74], rescuing endothelial function [75][76][77], inhibiting the activation and adhesion of monocytes [78], attenuating growth and migration of VSMCs [76,79,80], altering proliferation and apoptosis of VSMCs [80][81][82] and macrophages [83], as well as decreasing cytokine secretion in macrophages of [84].…”
Section: Discussionmentioning
confidence: 99%
“…and stem cell [3,4], no specific treatment exists for these diseases. Recently, several lines of evidence showed that somatostatin (SOM) has protective effects against central nervous system, pancreatic and gastrointestinal tract diseases [5][6][7], but the role of SOM in ALI remains to be clarified.…”
mentioning
confidence: 99%